(untitled) (Ustozlar uchun, 2026)
Equivalence in translation refers to the degree to which the translated text accurately reflects the meaning, style, and communicative effect of the original text. In modern translation studies, equivalence is considered a central concept because translators must ensure that messages are conveyed clearly across linguistic and cultural boundaries[1]. This paper reviews key theoretical frameworks, including Nida’s dynamic equivalence, Catford’s formal equivalence, and Koller’s equivalence types.